Qānūn Aḥwal Al-Shakṣiyyah Al-‘Irāqiyyah: Qira’ah Qanūn Al-Waṣiyyah Al-Wājibah - Syafa'at, Abd. Kholiq (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2013)
The Iraqi Personal Status Law has been amended several times by the Iraqi legislators in order to take into account the interests of the people, and the Iraqi legislators amend the Iraqi legislators to question the Iraqi street who want justice and equality in the distribution of inheritance, and the Iraqi legislators take into account in amending the Iraqi Personal Status Law, especially with regard to the provision of the obligatory will on several matters, highlighting them: A- Justice according to the words of the Almighty: The law of personal status in some Arab countries that have already been applied before the Iraqi Personal Status Law c. Opinions and doctrines of jurisprudence that are consistent with the custom and custom of Iraqi citizens, and according to the audience of fundamentalists, the rule of custom is used in deriving legal rulings.